A Systematic Review of Culturally Responsive Approaches to Child and Adolescent Mental Health Care in Ethiopia - Meshesha, Hana Shewamoltot; Johnson, Veronica (Frontiers in Sociology, 2021)
In 2012/13, the prevalence of child mental illness was estimated to be between 12% and 25% in Ethiopia. The Federal Ministry of Health is currently considering the implementation of the second national mental health strategy guided by the World Health Organization’s pyramid model for an optimal mix of services. This model states self-care as the fundamental concept and practice that can be facilitated by the formal and informal sectors surrounding an individual. Despite this remarkable move towards endorsing contemporary approaches to mental health services, Ethiopia struggles with a limited number of knowledgeable and skilled mental health professionals. Furthermore, the number of child/adolescent mental health professionals are few. This systematic review aims at identifying the main challenges Ethiopia might face while implementing the pyramid model. We will suggest ways to bridge the gap between the need for child/adolescent trained mental health professionals and training mental health professionals informed with the value of integrating the concepts of the pyramid model into the system of mental health care for Ethiopians. The paper also discusses the importance of integrating the Wellness based mental health approach into mental health professionals’ training as a means of developing a culturally responsive approach to child and adolescent services. This review provides implications for further studies and mental health policy, systems and services in Ethiopia.